2016
DOI: 10.4103/0971-5916.182618
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of phosphorylated heat shock protein 27 (pHSP27) are associated with bone mineral density in pre- & postmenopausal women: A pilot study

Abstract: Background & objectives:Phosphorylated heat shock protein 27 (pHSP27) has been implicated in the pathogenesis of osteoporosis. Oxidative stress and proinflammatory cytokines, which are known to be involved in aetiology of osteoporosis, can trigger HSP27 phosphorylation. Since pHSP27 is present in circulation, it was hypothesized that serum pHSP27 would be elevated in low bone mineral density (BMD) condition and might serve as an indicator of osteoporosis/osteopenia. Hence, the aim of this study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We found that heat shock protein 27, also known as heat shock protein beta-1 (HSPB1), was distinctly upregulated in low BMD condition in both premenopausal and postmenopausal categories [ 42 ]. Validation revealed that total HSP27 (tHSP27) and phosphorylated HSP27 (pHSP27) were elevated in low BMD condition in both categories not only in monocytes but also in sera [ 42 , 43 ]. Interestingly, pHSP27 exhibited a higher odds ratio than tHSP27 to predict low BMD, irrespective of menopausal status [ 43 ].…”
Section: Monocyte Protein Profiling In Low Versus High Bmd Conditimentioning
confidence: 99%
See 2 more Smart Citations
“…We found that heat shock protein 27, also known as heat shock protein beta-1 (HSPB1), was distinctly upregulated in low BMD condition in both premenopausal and postmenopausal categories [ 42 ]. Validation revealed that total HSP27 (tHSP27) and phosphorylated HSP27 (pHSP27) were elevated in low BMD condition in both categories not only in monocytes but also in sera [ 42 , 43 ]. Interestingly, pHSP27 exhibited a higher odds ratio than tHSP27 to predict low BMD, irrespective of menopausal status [ 43 ].…”
Section: Monocyte Protein Profiling In Low Versus High Bmd Conditimentioning
confidence: 99%
“…Validation revealed that total HSP27 (tHSP27) and phosphorylated HSP27 (pHSP27) were elevated in low BMD condition in both categories not only in monocytes but also in sera [ 42 , 43 ]. Interestingly, pHSP27 exhibited a higher odds ratio than tHSP27 to predict low BMD, irrespective of menopausal status [ 43 ]. Performance characteristics exhibited by pHSP27 and collagen type 1 cross-linked C-telopeptide (CTX-1) were comparable; however, pHSP27 showed lower sensitivity than CTX-1 and lower or comparable specificity than CTX-1 [ 43 ].…”
Section: Monocyte Protein Profiling In Low Versus High Bmd Conditimentioning
confidence: 99%
See 1 more Smart Citation